1995
DOI: 10.1007/s002620050184
|View full text |Cite
|
Sign up to set email alerts
|

Protective specific immunity induced by cyclophosphamide plus tumor necrosis factor ? combination treatment of EL4-lymphoma-bearing C57BL/6 mice

Abstract: A combination treatment protocol initiated 12 days after tumor injection, when the tumor was large, by administering cyclophosphamide (CY, 150 or 250 mg/kg) intraperitoneally followed by intravenous tumor necrosis factor alpha (TNF alpha, 1000 units injection) on days 13, 16, 18, 21, and 23, resulted in about 60% long-term survival (i.e., survival for at least 60 days) in the syngeneic C57BL/6 mouse/EL4 lymphoma model system. The establishment of a specific antitumor immune memory and its possible therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This immunity was correlated with the presence of anti-EL4 CD8 + CD44 + CTLs [16][17][18]20], but no adoptive transfer experiments were reported. Interestingly, it was noted that in C57BL/6 mice that received a curative cyclophosphamide plus TNF-α combination, there was initially thymic involution followed by regrowth [15,18]. This phenomenon may mirror the situation in nude mice where "space" for expansion of anti-tumor T cell clones is available due the paucity of T cells.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This immunity was correlated with the presence of anti-EL4 CD8 + CD44 + CTLs [16][17][18]20], but no adoptive transfer experiments were reported. Interestingly, it was noted that in C57BL/6 mice that received a curative cyclophosphamide plus TNF-α combination, there was initially thymic involution followed by regrowth [15,18]. This phenomenon may mirror the situation in nude mice where "space" for expansion of anti-tumor T cell clones is available due the paucity of T cells.…”
Section: Discussionmentioning
confidence: 95%
“…Studies by others have shown that if immunocompetent (C57BL/6) mice transplanted with syngeneic EL4 lymphoma cells are cured of their tumor by a chemotherapy-cytokine combination -they develop life-long immunity and reject re-implanted EL4 lymphomas [15][16][17][18]. The chemotherapy-cytokine treatments included cyclophosphamide plus TNF-α [15,16] [18] and doxorubicin plus IL-2 [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented here and in previous reports from this laboratory Ehrke et al, 1995;Ho et al, 1993a;Ho et al, 1993b) are consistent with the possibility that the thymus might serve such a role. In addition to the establishment of long-term anti-tumor cytolytic T cell memory in the thymus of the cured mice, the following were also found to be associated with an effective therapy: 1) an approximate 10-fold depletion of thymus cellularity (2-3 days after treatment) followed by thymic repopulation by days 30-60 (Krawczyk et al, 1995); 2) thymic anti-tumor cytolytic effector activity could not be stimulated ex vivo until approximately day 30, but thereafter was responsive for the life of the mouse (this study and Krawczyk et al, 1995;Ehrke et al, 1995); 3) premature termination of treatment resulted in the rapid onset of tumor-induced death, indicating the prolonged persistence of malignant cells Ho et al, 1993b); 4) a coincidence between the appearance of specific thymic anti-tumor cytolytic potential and the time at which treatment could be terminated (i.e., systemic tumor had been eradicated); and 5) a shift in the CD44 positivity from predominately the immature CD4 ϩ CD8 ϩ thymocytes to the mature CD4 Ϫ CD8 ϩ thymocytes. Singly, each observation is similar to that made by others in studies of the development of long-term memory and/or germinal centers.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated, if such combinations are to be successful clinically, that a much better understanding of the host parameters that play critical roles in the overall efficacy of the therapies must be gained. Toward this end, our laboratory has been studying the widely used anti-cancer agents doxorubicin (DOX, also known as Adriamycin) and cyclophosphamide in combination with certain cytokines, e.g., IL-2 and TNF-␣, in a syngeneic mouse tumor model system, i.e., C57BL/6 mice bearing EL4 lymphoma implanted s.c. (Ehrke et al, , 1996(Ehrke et al, , 1998aKrawczyk et al, 1995;Ho et al, 1993a,b). In this model, all mice implanted with as few as 10 EL4 cells die of progressive disease, lymphoid cells from naive (i.e., without tumor) C57BL/6 mice do not respond to stimulation with EL4 cells in culture, and at no time is anti-tumorspecific cytolytic effector activity detectable in fresh cell preparations of lymphoid organs from untreated tumor-bearing animals.…”
mentioning
confidence: 99%